(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article presents the results of the study of the Aydar-Arnasay Lake System (ISP-OES), one of the largest reservoirs in the country, by optical emission spectrometric method. The hydrochemical process of water in this lake area is not stable. Monitoring of the ecological status of the lake water was carried out using a stationary monitoring network, modern equipment and monitoring methods, which allows to assess the regularity of anthropogenic changes in the environment and biological system problems that have toxic effects.